The making of modern Japan - Jansen, Marius B. (Cambridge, Mass. Belknap Press of Harvard University Press, 2000)
"Jansen covers the making of the modern state, the adaptation of Western models, growing international trade, the broadening opportunity in Japanese society with industrialization, and the postwar occupation reforms imposed by General MacArthur. Throughout, the book gives voice to the individuals and views that have shaped the actions and beliefs of the Japanese, with writers, artists, and thinkers as well as political leaders given their due." "The story this book tells, though marked by profound changes, is also one of remarkable consistency, in which continuities outweigh upheavals in the development of society, and successive waves of outside influence have only served to strengthen a sense of what is unique and native to Japanese experience. The Making of Modern Japan takes us to the core of this experience as it illuminates one of the contemporary world's most compelling transformations."--BOOK JACKET.
1. Sekigahara -- 2. The Tokugawa State -- 3. Foreign Relations -- 4. Status Groups -- 5. Urbanization and Communications -- 6. The Development of a Mass Culture -- 7. Education, Thought, and Religion -- 8. Change, Protest, and Reform -- 9. The Opening to the World -- 10. The Tokugawa Fall -- 11. The Meiji Revolution -- 12. Building the Meiji State -- 13. Imperial Japan -- 14. Meiji Culture -- 15. Japan between the Wars -- 16. Taisho Culture and Society -- 17. The China War -- 18. The Pacific War -- 19. The Yoshida Years -- 20. Japan since Independence.
Includes bibliographical references (p. [795]-840) and index.
Keywords: Japan -- Hiotory -- Tokugawa period, 1600-1868.; Japan -- History -- Meiji period, 1868-1912.